Meta-Analysis the Association between Chronic Obstructive Pulmonary Disease Comorbidity and COVID-19 Mortality - Pamogsa Ratri Adha Daniyar; Agus Kristiyanto; Setyo Sri Rahardjo (Journal of Epidemiology and Public Health, 2021)
disease that hit the world community at the end of 2019. The risk of death from COVID-19 is highly dependent on age and previous health conditions. COVID-19 severe and critical symptoms are more commonly found in older patients and patients who have chronic comor